If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4 = 2(7 + -1x) Reorder the terms: -4 + 3x = 2(7 + -1x) -4 + 3x = (7 * 2 + -1x * 2) -4 + 3x = (14 + -2x) Solving -4 + 3x = 14 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -4 + 3x + 2x = 14 + -2x + 2x Combine like terms: 3x + 2x = 5x -4 + 5x = 14 + -2x + 2x Combine like terms: -2x + 2x = 0 -4 + 5x = 14 + 0 -4 + 5x = 14 Add '4' to each side of the equation. -4 + 4 + 5x = 14 + 4 Combine like terms: -4 + 4 = 0 0 + 5x = 14 + 4 5x = 14 + 4 Combine like terms: 14 + 4 = 18 5x = 18 Divide each side by '5'. x = 3.6 Simplifying x = 3.6
| 48-4t=4t | | 3(y-7)= | | (4x-2)=-1+2x | | 5-3(2x+9)=50 | | 0.4(x+90)+0.2x=45 | | X^2+4x-169=0 | | -5x+6=9-6x | | 9+5a=-26 | | t-22=-23 | | 8n-8=5n+7 | | -16t^2+40t-65=0 | | -16t^2+40t+65=0 | | 1.5(4d-2)=d+5 | | 4x-2=-6+5x | | 2x^2-48x+48=0 | | n-3=17-4n | | 7x+10=5x+6 | | 2+2y=3 | | z-12/4=z/16 | | 2x-6(x+3)=2600 | | 3/4(z-5)=12z | | 2x-9=6x+7 | | 7x+6=5x+10 | | 6x+9x=-60 | | 4x-9x+1=21 | | x^3+7x^2+5x+35=0 | | 6x+3(x+1)=9x+6 | | (b+6)=7 | | 2+3d+d= | | -4(n-4)-23=7 | | 3b-24=11b | | 15=-d+8 |